Crop Residue Quality Assessment and Measurement of Wastage under Different Storage Conditions - International Livestock Research Institute (International Livestock Research Institute, 2014)
Physical and chemical evaluation of crop residue samples and measurement of biomass wastage. To learn more about this dataset, please visit the ILRI Datasets Portal http://data.ilri.org/portal/dataset/crop_residue_mgm